KAJIAN YURIDIS PEMAKAMAN PROTOKOL KESEHATAN DITINJAU DARI HAK UNTUK MENDAPATKAN KEBENARAN INFORMASI PASAL 14 AYAT (1) UNDANG – UNDANG HAK ASASI MANUSIA: KAJIAN YURIDIS PEMAKAMAN PROTOKOL KESEHATAN DITINJAU DARI HAK UNTUK MENDAPATKAN KEBENARAN INFORMASI PASAL 14 AYAT (1) UNDANG – UNDANG HAK ASASI MANUSIA - Retno, Evi; Kuswanto, Heru (Lex Journal: Kajian Hukum & Keadilan, 2021)
A The Government's efforts in the Covid-19 pandemic issue regarding the issue of public dissatisfaction with the handling carried out by several unscrupulous medical teams in this pandemic in various existing hospitals. Many members of the community feel dissatisfied and agree with having experienced some kind of coercive action, including when they are going to be isolated in hospital based only on the results of their suspicion or concern that they will be exposed to the Covid-19 Virus. In other cases, the medical team forced the bodies of people who died from non-Covid-19 diseases to be buried following the covid-19 funeral protocol. Community complaints related to determining the status of ODP, PDP and OTG patients. Many patients under surveillance (PDP) who died were buried according to the Covid-19 protocol, but the swab test results were negative. The solution to cases like this did not happen, the hospital should have accelerated the examination of the swab test in the laboratory. Many incidents of bodies were buried with the Covid protocol but the results of the swab test were negative, causing a misunderstanding between the hospital and the family, and also so that the family does not consider funerals according to the Covid-19 protocol as a matter of human rights (HAM). The reason is, there were those who were declared ODP and PDP died during the treatment process at the hospital. But the results of the swab test are yet to come out. apologized that the hospital immediately conducted a swab test on the patient. The laboratory must also prioritize all those lying in the hospital. The family did not accept it because their relatives were buried according to the Covid-19 protocol, because when ODP and PDP were admitted to the hospital, the patient was immediately asked to sign ready to follow the Covid-19 protocol, even though it was not certain that the patient was sick because of Covid-19. It's been buried and then the results come out. Things like this are definitely obtained from the community. negative family of covid-19 but why buried according to covid-19 protocol. Because the community also needs certainty, not only because of suspicion, then the patient immediately serves covid-19 and the patient should not be left waiting for days for the results of the swab test. Keywords: Covid-19, Funeral, Human Rights, protocol,patient